Summer school: effects in fourth and fifth grades - Koehn, Karen K., author; Cooner, Donna, advisor; Gloeckner, Gene W., committee member; Lucero, Rodrick, committee member; O'Donnell-Allen, Cindy, committee member (Colorado State University. Libraries, 2014)
Summer school has long been viewed as a viable method of decreasing the time out of school for students and thereby increasing student achievement for summer school attendees. A search of the literature reveals that many summer school programs are effective in preventing reading achievement loss of elementary students, particularly for students who qualify for free or reduced lunch. The purpose of this study was to determine both the short and long term effects of a summer school program on students attending summer school following their fourth grade year. Independent sample t tests were performed to determine the difference in reading MAP score growth for students attending summer school and non-attendees. Comparisons were made based on socioeconomic status. Results showed no significant difference in gain scores between attendees and non-attendees immediately following summer school or at the end of the fifth grade year, regardless of socioeconomic status. Implications for action and recommendations for further study are included at the conclusion of this study. These include closer examination of the grade levels and type of students experiencing the greatest benefit from summer school programs, the type of summer program producing the best results, and consideration for the needs of the specific school community.
Keywords: summer loss; intermediate grades; summer school; academic achievement; economically disadvantaged